Kedudukan Dalil Al-Quran dalam Pertimbangan Putusan Sengketa Ekonomi Syariah - Elizatun, Elizatun; Mujib, Abdul; Chaerul Firdaus, Muh. Nur Ridho (Hukum Islam, 2025)
The purpose of this research is to analyze the position of the Quranic verse in the consideration of the judge's decision and to find out the reasons for the judge to use the Quranic verse as one of the considerations in deciding sharia economic disputes. This research is a descriptive qualitative research with normative juridical method and case approach. The main data source is 20 sharia economic case decisions with a time span from 2015-2025 as a sample selected through purposive sampling technique. The type of data collection used is in the form of writing with literature studies and also communication methods in the form of interviews. The results of this study indicate that the position of the Koran in the consideration of judges' decisions in sharia economic disputes is a binding legal norm, but there is no obligation to include it. This means that the Quranic argument is only a complement to the judge's argument. However, even though there is no obligation to include it, a religious court judge is obliged to decide cases based on Islamic law, either using the Fatwa DSN MUI or KHES which is an applied law based on the arguments of the Koran. Then, the reason why judges use Quranic verses as one of the considerations in deciding sharia economic disputes is to strengthen the legal basis used in the decision and provide transparency and clarity regarding sharia principles.